Prediction of vibration radiation noise from shell of straw crushing machine. (October 2021) - Xuejian, Lun; Can, Li; Zhiping, Zhai; Yuezheng, Lan; Shiming, Gan
In order to predict the radiation noise of the vibrating shell of the straw crusher in the design phase, the computational fluid dynamics–discrete element coupling method is initially used to simulate the airflow–straw coupled flow field in the straw crusher, and the pulsating pressure generated by the coupled flow field is applied to the inner surface of the shell of the crusher. Then, the harmonic response of the shell is analyzed, and its results are used to be the acoustic boundary condition. Finally, the finite element and acoustic boundary element combined test methods are used to predict vibration noise of the straw crusher shell. The results indicate that the produced vibration noise of the straw crusher shell changes as the excitation frequency of the rotor rotation changes. The maximum vibration noise is achieved at the excitation fundamental frequency, and radiation noises at the harmonic frequencies decrease as the frequency increases. The simulated value of the sound pressure level of each measuring point at the excitation fundamental frequency and harmonic frequencies is basically the same as those of the experiment. Moreover, it is found that the maximum difference between the simulated and experimental value of measuring points is 1.69 dB(A). Therefore, it is concluded that the numerical model of the vibration radiation noise is accurate. The vibration noise of the shell at the inlet is the largest, and the main noise source of the vibration radiation noise is the dipole sound source of the rotating hammer rotor. The corresponding design method provides the reference for the low-noise design of straw crushers.